FAKTOR-FAKTOR YANG MEMPENGARUHI KEBUTUHAN MODAL KERJA PADA PERUSAHAAN MANUFAKTUR YANG TERDAFTAR DI BURSA EFEK INDONESIA - Sitompul, Johari; Ndruru, Fiktor (JURNAL NERACA AGUNG, 2020)
This study aims at determining the effect of leverage, profitability, both simultaneous and partial company size on working capital requirements in manufacturing companies in the basic and chemical industry sub-sectors on the Stock Exchange in 2016-2018. The population in this study amounted to 48 companies with a sample of 14 companies. This data collection technique uses a purposive sampling technique that is sampling using certain criteria, namely: companies manufacturing basic and chemical sub-sectors listed on the Indonesia Stock Exchange in 2016-2018 and not experiencing losses during the study period in 2016-2018. Data was analyzed by using Multiple Linear Regression Analysis. The analysis proves partially leverage does not have a significant effect on working capital requirements, because the value of t count < t table (0.973 ˂ 2.024), and the t-test sig has a result greater than 0.05 (0.337 ˃ 0.05). Profitability has a negative and significant effect on working capital requirements because the t-value ˃ t table (-3,200 ˃ 2,024), and in the t-test sig is smaller than 0.05 (0.003 ˂ 0.05). The size of the company has no significant effect on the need for working capital with t ˂ t table (-0.155 ˂ 2.024), and the t-test sig is greater than 0.05 (0.878 ˃ 0.05). F test results explain that the DER, ROA, and UP variables simultaneously have a significant effect on working capital requirements because the F count value is 4.088 while the F table is 2.850, so the F count ˃ F table (4.088 ˃ 2.850). Determination coefficient test results are 0.184 or 18.40% explains that the DER, ROA and UP variables simultaneously have a significant effect on the variable needs of working capital, 18.40% changes from the variable needs of working capital, while the remaining 81.60% is caused by other variables Outside this research is capital structure and business risk.